ANALISIS DAYA DUKUNG SUMBER DAYA AIR UNTUK MENINGKATKAN KETERSEDIAAN AIR DI KABUPATEN BANDUNG, JAWA BARAT - Parahita, Fayra; Baskoro, Dwi Putro Tejo; Darmawan, Darmawan (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Cisangkuy watershed is the main source to meet the demand for raw water in Bandung city and Bandung Regency. The current hydrological condition has decreased as indicated by high fluctuations in river flow. The objectives of this study were to evaluate land use changes and water availability in the Cisangkuy watershed and to develop recommendations for land use to increase water availability in Bandung Regency based on the results of the hydrological simulation. There are some data used for analysis including land use map, spatial planning maps of Bandung regency, population numbers, industrial water demand, discharge, rice field area, freshwater fish pond area and the number of livestock. In summary, this research phase begins with an evaluation of land use changes , then calculates the water balance using the SWAT model. Changes in land use in the Cisangkuy watershed from 2007-2017 occurred from vegetated land cover to non-vegetation, which had an impact on the hydrological system and the availability of water in the Cisangkuy watershed. The potential for surface water supply in the Cisangkuy watershed with the existing scenario (in 2017) is 495.58 million m3 and the total user consumption water demand is 592.78 million m3, so there is water balance deficit about 97.20 million m3. The application of scenarios for improving land management by increasing the area of mixed dry land agriculturalwith agroforestry methods, reforestation on plantation forest land, applying infiltration wells in settlements and applying terraces to paddy fields provides a fairly good hydrological response to reduce the raw water deficit from 174,91 million to 63.98 million m3.Keywords: land use change, water supply, water demands, water balance, Cisangkuy Watershed